2014
DOI: 10.2754/avb201483020107
|View full text |Cite
|
Sign up to set email alerts
|

Induction of accessory corpus luteum in cows by gonadotropin-releasing hormone administrated after insemination

Abstract: Sufficiency of progesterone limits conception rate in dairy cows. This study evaluates the effect of gonadotropin-releasing hormone on induction of accessory corpus luteum, progesterone concentrations and pregnancy in dairy cows. The hormone (0.05 mg) was administrated intramuscularly to cows with one corpus luteum on day 5-7 (Group E1, n = 57) or 11-13 (Group E2, n = 40) after insemination; control groups C1 (n = 54) and C2 (n = 41) were not treated. Detection of pregnancy by ultrasound examination and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
2
7
1
1
Order By: Relevance
“…The occurrence of 2 CL was 15% in cows treated on days 0 and 12 (Lopez-Gatius et al 2006) or 17.7% in cows treated on days 28-34 (Bech-Sabat et al 2009) after insemination. Occurrences of 2 CL in cows treated on day 7 or on days 5-7 vs cows treated on day 13 or on days 11-13 after insemination were 54.2 or 43.9% vs 24.7 or 33.5% in our previous studies Musilova et al 2014). In this study we found a similar occurrence of 2 CL (42.2%) in the same period after treatment (day 28).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The occurrence of 2 CL was 15% in cows treated on days 0 and 12 (Lopez-Gatius et al 2006) or 17.7% in cows treated on days 28-34 (Bech-Sabat et al 2009) after insemination. Occurrences of 2 CL in cows treated on day 7 or on days 5-7 vs cows treated on day 13 or on days 11-13 after insemination were 54.2 or 43.9% vs 24.7 or 33.5% in our previous studies Musilova et al 2014). In this study we found a similar occurrence of 2 CL (42.2%) in the same period after treatment (day 28).…”
Section: Discussionsupporting
confidence: 78%
“…Usual rates of early embryo doi: 10.17221/46/2016-CJAS mortality, late embryo/early fetal mortality, and late abortion in cows are 20-45%, 8-17.7%, and 1-4%, respectively (Humblot 2001). Insignificant lower late embryo/early fetal mortalities in the presence of accessory CL have been described by Bartolome et al (2006), Bech-Sabat et al (2009), andMusilova et al (2014). We did not find significant differences in pregnancy loss between treated cows bearing 1 or 2 CL in this trial either.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is also in agreement with the findings of Musilová et al . [ 18 ], who reported that administration of GnRH on day 5-7 or 11-13 after insemination was efficient to induce accessory CL and increase the concentration of serum progesterone. Several studies have reported a positive effect of GnRH administration on pregnancy rates [ 19 - 21 ], but in few other studies, GnRH administration failed to exhibit a positive impact on pregnancy rate [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to buffalo-cows treated with GnRH in our study, [46] showed that GnRH administered 12 days post insemination significantly increased serum P4 on day 18 post-insemination in dairy cattle. Also, administration of GnRH injection in cows at 11-13 day post-AI have been reported to cause ovulation of second follicular wave follicle, induce accessory CL formation, stimulate CL function, induce increase plasma P4, reduce estrogen production and have a positive effect on embryo survival and ultimately improving fertility responses [45].…”
Section: Serum P4 Profile On Different Post-mating Daysmentioning
confidence: 99%